How will Russia's invasion of Ukraine affect global food security? - Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
The unfolding crisis in Ukraine has roiled commodity markets and threatens global food security. Ongoing fall out from the COVID-19 pandemic and other factors have already driven up food prices. Poor harvests in South America, strong global demand, and supply chain issues have reduced grain and oilseed inventories and driven prices to their highest levels since 2011–2013. Vegetable oil prices have also been at record levels, reflecting the short South American soybean crop, reduced palm oil supplies due to harvest problems in Malaysia, and sharply increased use of palm and soybean oil for biodiesel production. Prices of key energy-intensive inputs like fuel, fertilizer, and pesticides have also been at near-record levels.